Intensification of microbial exopolysaccharide ethapolan synthesis under Acinetobacter sp. IMV B-7005 cultivation on sunflower oil - Ivahniuk, Mykola; Pirog, Tatiana (My University, 2014)
Microbial exopolysaccharides (EPS) by the ability of their solutions to change the rheological properties of aqueous systems are widely used in various industries. In recent years, research on the use of industrial waste (including oil-containing) to obtain practically valuable microbial metabolites intensified. Мікробні екзополісахариди (ЕПС) завдяки здатності їхніх розчинів до змінення реологічних характеристик водних систем широко застосовуються у різних галузях промисловості. Останніми роками активізувалися дослідження з використання промислових відходів для одержання практично цінних мікробних метаболітів, в тому числі й олієвмісних.
Keywords: кафедра біотехнології і мікробіології